Pengaruh Kepuasan Kerja Terhadap Kualitas Pelayanan dan Loyalitas Kerja Pada Karyawan di Rumah Makan Palinggihan Cirebon - Tarigan, Emenina; Sembiring, Vienna Artina; Taviprawati, Ervina (Jurnal Ilmiah Pariwisata, 2021)
This study aims to determine (1) job satisfaction on service quality; (2) job satisfaction on job loyalty. The method used in this study is simple regression analysis, the sampling technique in this study is a saturated sampling technique, the population is the same as the sample, namely 40 respondents. The results of the study of job satisfaction have a significant effect on service quality with a t-count value of 4.669 > t-table 2.024, while job satisfaction has a significant effect on job loyalty with a t-count value of 2.975 > t-table 2.024. The higher the job satisfaction of employees, the higher the quality of services provided to employees and customers. Then the higher the employee's job satisfaction, the higher the employee's work loyalty given to the company. For the management of the Mostgihan restaurant, it provides a remuneration system based on performance, length of work, career path, and old age insurance. Employee welfare will have an impact on increasing job satisfaction. In improving the quality of service, the Panggihan restaurant provides training for its employees so that employees are more confident in communicating with guests and have expertise in serving in order to achieve good service quality. Keywords: Restaurant, Job Satisfaction, Service Quality, Work Loyalty